Foamed resin particles and foamed particles

JP2026166718APending Publication Date: 2026-10-14JSP CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059860
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0016】 本発明に係る一の態様によれば、ブロッキングおよび成形体の外観不良を抑制することが可能な発泡性樹脂粒子を提供できる。また、本発明の他の形態によれば、ブロッキングが抑制され、かつ成形体の外観不良を抑制することが可能な発泡粒子を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166718000001_ABST
    Figure 2026166718000001_ABST
Patent Text Reader

Abstract

The present invention provides foamed resin particles capable of suppressing blocking and defects in the appearance of molded articles, and foamed particles that suppress blocking and also suppress defects in the appearance of molded articles. [Solution] According to one aspect of the present invention, foamable resin particles are provided, comprising a resin particle body having an acrylonitrile-styrene copolymer as a base resin and a foaming agent, wherein the foamable resin particles contain a brominated styrene-butadiene copolymer and the moisture content of the foamable resin particles is 1% by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to expandable resin particles and expanded particles.

Background Art

[0002] Resins composed of acrylonitrile-styrene copolymers are known to be superior in oil resistance, chemical resistance, heat resistance, and the like, as compared with polystyrene.

[0003] Expandable particles based on an acrylonitrile-styrene copolymer may contain a flame retardant in order to improve flame retardancy (see, for example, Patent Document 1). As the flame retardant, brominated bisphenol A derivatives are mainly used.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problem to be Solved by the Invention

[0005] However, when a brominated bisphenol A derivative is contained as a flame retardant in expandable particles based on an acrylonitrile-styrene copolymer, blocking, in which expanded particles are fused to each other during expansion of the expandable particles, is liable to occur, and the appearance of a molded article may be deteriorated.

[0006] The present invention has been made to solve the above problems. That is, an object of the present invention is to provide expandable resin particles capable of suppressing blocking and poor appearance of a molded article, and expanded particles in which blocking is suppressed and poor appearance of a molded article can be suppressed.

Means for Solving the Problem

[0007] [1] Foamable resin particles comprising a resin particle body having an acrylonitrile-styrene copolymer as a base resin and a foaming agent, wherein the foamable resin particles contain a brominated styrene-butadiene copolymer and the moisture content of the foamable resin particles is 1% by mass or less.

[0008] [2] The foamed resin particles according to [1], wherein the amount of brominated styrene-butadiene copolymer blended is 0.2 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin.

[0009] [3] The foaming resin particles according to [1] above, wherein the amount of brominated styrene-butadiene copolymer blended is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the base resin.

[0010] [4] The foamed resin particles according to any one of the above [1] to [3], wherein the acrylonitrile component content in the acrylonitrile-styrene copolymer is 10% by mass or more and 50% by mass or less.

[0011] [5] Foaming resin particles according to any one of the above [1] to [4], wherein the foaming agent comprises pentane and butane.

[0012] [6] The foamable resin particle according to any one of the above [1] to [5], wherein a fatty acid amide is attached to the surface of the resin particle body, and the melting point of the fatty acid amide is 60°C or more and 140°C or less.

[0013] [7] The foaming resin particles according to [6] above, wherein the ratio (X / Y) of the amount of brominated styrene-butadiene copolymer blended (X) to the amount of fatty acid amide attached (Y) is 10 or more and 100 or less.

[0014] [8] Foamed particles having an acrylonitrile-styrene copolymer as the base resin, wherein the foamed particles contain a brominated styrene-butadiene copolymer, and the surface bubble diameter of the foamed particles is 40 μm or more and 60 μm or less.

[0015] [9]The expanded bead according to the above [8], wherein the blending amount of the brominated styrene-butadiene copolymer is 0.2 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the base resin.

Effects of the Invention

[0016] According to one aspect of the present invention, expandable resin particles capable of suppressing blocking and poor appearance of a molded article can be provided. According to another aspect of the present invention, expanded beads in which blocking is suppressed and poor appearance of a molded article can be suppressed can be provided.

Brief Description of the Drawings

[0017] [Figure 1] Figure 1 is a scanning electron microscope (SEM) image of the expanded bead according to Example 1. [Figure 2] Figure 2 is an SEM image of the expanded bead according to Comparative Example 2. [Figure 3] Figure 3 is an SEM image of the expanded bead according to Comparative Example 3. [Figure 4] Figure 4 is an SEM image of the expanded bead according to Comparative Example 4. [Figure 5] Figure 5 is a photograph of the molded article according to Example 1. [Figure 6] Figure 6 is a photograph of the molded article according to Comparative Example 1. [Figure 7] Figure 7A is an SEM image of the expanded bead according to Example 8 observed at a magnification of 60 times, and Figure 7B is an SEM image of the expanded bead according to Example 8 observed at a magnification of 100 times. [Figure 8] Figure 8A is an SEM image of the expanded bead according to Example 10 observed at a magnification of 60 times, and Figure 8B is an SEM image of the expanded bead according to Example 10 observed at a magnification of 100 times.

Modes for Carrying Out the Invention

[0018] Hereinafter, the expandable resin particles and expanded beads according to the embodiments of the present invention will be described.

[0019] <<Expandable Resin Particles>> The expandable resin particles include a resin particle body using an acrylonitrile-styrene copolymer as a base resin, a blowing agent, and a brominated styrene-butadiene copolymer as a flame retardant. The water content of the expandable resin particles is 1% by mass or less. In the present invention, the base resin means that the acrylonitrile-styrene copolymer is present as the main component of the resin component constituting the resin particle body. The content of components other than the acrylonitrile-styrene copolymer in the base resin is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0020] <Resin Particle Body> In the acrylonitrile-styrene copolymer constituting the resin particle body, the content of the acrylonitrile component is preferably 10% by mass or more and 50% by mass or less, and the content of the styrene component is preferably 50% by mass or more and 90% by mass or less (provided that the total of the acrylonitrile component and the total of the styrene component is 100% by mass). When the content of the acrylonitrile component is 10% by mass or more, the decrease in oil resistance of the molded article can be suppressed, and when it is 50% by mass or less, good foamability and moldability can be obtained. The lower limit of the content of the acrylonitrile component is more preferably 15% by mass or more or 20% by mass or more, and the upper limit is more preferably 40% by mass or less or 30% by mass or less. The content of the acrylonitrile component in the acrylonitrile-styrene copolymer can be determined by a known method such as pyrolysis gas chromatography analysis.

[0021] The weight average molecular weight of the acrylonitrile-styrene copolymer is preferably 100000 or more and 500000 or less. When this weight average molecular weight is 100000 or more and 500000 or less, the decrease in oil resistance of the molded article can be suppressed, and good foamability and moldability can be obtained. The lower limit of this weight average molecular weight is more preferably 150000 or more or 170000 or more, and the upper limit is more preferably 400000 or less or 300000 or less.

[0022] <Blowing Agent> The blowing agent is not particularly limited, but examples include saturated hydrocarbons having 3 to 5 carbon atoms. Examples of saturated hydrocarbons having 3 to 5 carbon atoms include propane, n-butane, i-butane, n-pentane, i-pentane, cyclopentane, neopentane, etc. Such saturated hydrocarbons can be used alone or in mixtures of two or more. As a blowing agent, a mixture of pentane and butane is more preferable from the viewpoint of the heat insulating performance of the foamed resin particles. Furthermore, the mass ratio of the mixture of pentane and butane is preferably 90:10 to 60:40, and more preferably 80:20 to 70:30 (provided that the total amount of pentane and butane is 100% by mass).

[0023] The foaming agent content is preferably 2% by mass or more and 6% by mass or less relative to the foamed resin particles. If the foaming agent content is 2% by mass or more and 6% by mass or less relative to the foamed resin particles, sufficient foaming properties can be imparted to the foamed resin particles based on acrylonitrile-styrene copolymer. The lower limit of the foaming agent content is more preferably 2.4% by mass or more and 2.6% by mass or more, and the upper limit is more preferably 5% by mass or less and 4% by mass or less.

[0024] <Brominated styrene-butadiene copolymer> Brominated styrene-butadiene copolymer refers to a brominated product of styrene-butadiene copolymer, and may be a block copolymer, a random copolymer, or a graft copolymer, with a block copolymer of polystyrene and brominated polybutadiene block being more preferable. The brominated styrene-butadiene copolymer used as a flame retardant is not included in the base resin.

[0025] The weight-average molecular weight of the brominated styrene-butadiene copolymer is preferably 1,000 to 200,000 in terms of polystyrene. The lower limit of this weight-average molecular weight is more preferably 2,000 or more, 5,000 or more, or 50,000 or more, and the upper limit is more preferably 175,000 or less, 150,000 or less, or 125,000 or less.

[0026] The bromine content of the brominated styrene-butadiene copolymer is preferably 60% by mass or more, in order to enhance the flame retardant effect. A bromine content of 63% by mass or more is more preferable. The above bromine content can be determined in accordance with JIS K7392:2009.

[0027] Brominated styrene-butadiene copolymer, 200°C, 100 sec -1 The melt viscosity in this case may be around 4000 to 8000 Pa·s.

[0028] The brominated styrene-butadiene copolymer preferably has the following structure. [ka] In the formula, X, Y, and Z are positive integers.

[0029] From the viewpoint of flame retardancy-imparting effect, the bromine content in the brominated styrene-butadiene copolymer is preferably 60% by weight or more, and more preferably 63% by weight or more. The above bromine content can be determined in accordance with JIS K7392:2009.

[0030] Commercially available brominated styrene-butadiene copolymers include "Emerald Innovation® 3000" from Chemtura Japan Co., Ltd. and "FR-122P" from ICL-IP.

[0031] The amount of brominated styrene-butadiene copolymer blended is preferably 0.2 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin. When the amount of brominated styrene-butadiene copolymer blended is 0.2 parts by mass or more and 10 parts by mass or less, the increase in the moisture content of the foamed resin particles is suppressed and higher flame retardancy can be achieved. The lower limit of this blending amount is more preferably 0.5 parts by mass or more, 0.8 parts by mass or more, or 1.2 parts by mass or more, and the upper limit is more preferably 5 parts by mass or less, 4 parts by mass or less, or 3 parts by mass or less.

[0032] The amount of brominated styrene-butadiene copolymer in the foamed resin particles can be estimated from the amount added, for example, if the amount added is known. It can also be calculated by measurement from samples such as foamed resin particles or foamed particles. For example, the sample can be pretreated by reprecipitation with methyl ethyl ketone-methanol solvent, evaporation of methanol to dryness, and separation of methanol-soluble components, and then the brominated styrene-butadiene content can be measured by high-performance liquid chromatography. The bromine content of the brominated styrene-butadiene copolymer can be measured by X-ray fluorescence analysis. The amount of brominated styrene-butadiene copolymer is approximately equal to the amount of brominated styrene-butadiene copolymer added during the manufacturing process of the foamed resin particles.

[0033] Furthermore, other commonly used flame retardants may be included as flame retardants, provided they do not hinder the intended effects of the present invention. Examples of other flame retardants include hexabromocyclododecane, tetrabromobisphenol A compounds, trimethylphosphate, and aluminum hydroxide.

[0034] <Fatty acid amide> It is preferable that fatty acid amides adhere to the surface of the resin particle body. The fatty acid amides may adhere to the entire surface of the resin particle body or to a part of the surface of the resin particle body. It is thought that the fatty acid amides become compatible with the base resin that is softened during the foaming process of the foamable resin particles and are dispersed unevenly on the surface of the foamable resin particles. These dispersed fatty acid amides become the starting point for cracks during the foaming process of the foamable resin particles and during the cooling process of the foamed particles after foaming. Therefore, by adhering fatty acid amides to the surface of the resin particle body, cracks can be formed uniformly on the surface of the foamed particles.

[0035] Furthermore, when fatty acid amides and flame retardants are used in combination, it becomes possible to effectively suppress the fire-spreading phenomenon that occurs when the foam burns. Here, the fire-spreading phenomenon refers to the phenomenon in which flames propagate only on the surface of the foam during combustion. The reason for the above effect when fatty acid amides and flame retardants are used in combination is thought to be that the adhesion of fatty acid amides causes cracks to form on the surface of the foam particles, which allows the foaming agent to dissipate and reduces the amount of volatile matter remaining in the mold.

[0036] As fatty acid amides, condensates of fatty acids and primary amines or condensates of fatty acids and secondary amines can be used. For example, as fatty acid amides, compounds such as erucic acid amide, oleic acid amide, stearic acid amide, and N-stearyl stearate amide can be used. These fatty acid amides may be used alone or in combination of two or more fatty acid amides.

[0037] The melting point of fatty acid amides is between 60°C and 140°C. By attaching fatty acid amides having a melting point within a specific range to the surface of the resin particle body, it is possible to make the softened base resin and fatty acid amides more compatible when foaming the foamable resin particles. As a result, cracks can be easily generated on the surface of the foamed particles. From the viewpoint of further enhancing these effects, the melting point of the fatty acid amide is preferably between 65°C and 120°C, and more preferably between 70°C and 100°C.

[0038] Furthermore, from the viewpoint of compatibility between fatty acid amides and acrylonitrile-styrene copolymers, the difference Tg-Tm between the glass transition temperature Tg of the acrylonitrile-styrene copolymer and the melting point Tm of the fatty acid amide is preferably 50°C or less, more preferably 25°C or less, and even more preferably 20°C or less.

[0039] The amount of fatty acid amide attached is preferably 0.01 parts by mass or more and 0.15 parts by mass or less per 100 parts by mass of the resin particle body. Furthermore, the ratio (X / Y) of the amount of brominated styrene-butadiene copolymer blended (X) to the amount of fatty acid amide attached (Y) is preferably 10 or more and 100 or less. When the amount of fatty acid amide attached (Y) and the ratio (X / Y) are within the above range, the length of the molten area when a fire run test is performed on the molded article can be effectively reduced, and the cooling time during molding can be shortened.

[0040] The lower limit of the amount of fatty acid amide attached is more preferably 0.02 parts by mass or 0.05 parts by mass or more per 100 parts by mass of the resin particle body, and the upper limit is more preferably 0.11 parts by mass or less or 0.09 parts by mass or less per 100 parts by mass of the resin particle body.

[0041] Furthermore, the lower limit of the above ratio is more preferably 15 or more or 20 or more, and the upper limit is more preferably 50 or less or 35 or less.

[0042] The amount of fatty acid amide attached can be measured, for example, by the following method: Dissolve the foamed resin particles in N,N-dimethylformamide (DMF). By performing gas chromatography analysis of this solution, the amount of fatty acid amide in the solution can be quantified.

[0043] Alternatively, the amount of fatty acid amide attached can be measured using the following method. First, the foamed resin particles are washed with a solvent that does not dissolve the base resin, such as methanol, to separate the resin particles from the attached material. This attached material is dissolved in DMF, and the amount of fatty acid amide in the solution can be quantified by gas chromatography analysis of the solution. The amount of fatty acid amide attached is approximately equal to the amount of fatty acid amide added during the manufacturing process of the foamed resin particles.

[0044] As the fatty acid amide, for example, fatty acid amides with 12 to 24 carbon atoms, such as oleic acid amide, erucic acid amide, and stearic acid amide, can be used. As the fatty acid amide, one type of fatty acid amide may be used, or two or more types of fatty acid amides may be used in combination. As the fatty acid amide, it is preferable to use an unsaturated fatty acid amide with 14 to 24 carbon atoms because it further reduces the length of the molten part when a fire run test is performed on the molded article, and among these, oleic acid amide is more preferable. A commercially available oleic acid amide is "Amide O" manufactured by Kao Corporation (melting point: 70-75°C).

[0045] Other coating agents may be used in combination with fatty acid amides. Examples of other coating agents include silica, glycerin monostearate, and hydroxyalkylamines.

[0046] <Moisture content> As described above, the moisture content of the foamed resin particles is 1% by mass or less. Preferably, this moisture content is 0.7% by mass or less, 0.6% by mass or less, or 0.5% by mass or less. The moisture content of the foamed resin particles can be measured by heating the foamed resin particles to vaporize the moisture and measuring the vaporized moisture using a Karl Fischer moisture meter. According to the present invention, by including a brominated styrene-butadiene copolymer as a flame retardant in the foamed resin particles, the moisture content in the foamed resin particles can be reduced, and as a result, the surface bubbles of the obtained foamed particles can be limited to a specific range. Furthermore, when the obtained foamed particles are molded in a mold, it is possible to obtain a molded article with excellent surface properties.

[0047] The foamed resin particles may contain additives such as foam regulators, pigments, slip agents, and antistatic agents, as long as they do not impair the effects of the present invention. The above additives are preferably contained in a proportion of 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the resin particle body.

[0048] <Method for manufacturing foamed resin particles> To produce foamed resin particles, first, styrene, acrylonitrile, brominated styrene-butadiene copolymer, polymerization initiator, etc., are suspended in an aqueous phase and subjected to suspension polymerization, and a foaming agent is impregnated to form foamed resin particles. Then, if necessary, dehydration, drying, and classification are performed, and then a coating agent such as fatty acid amide can be applied to the surface.

[0049] Suspension into the aqueous phase can usually be performed using a device equipped with a stirring blade. It is also preferable to add a suspension agent or surfactant to the aqueous phase. Furthermore, if necessary, suspension aids and flame retardants may be suspended in the aqueous phase in addition to styrene, etc.

[0050] The polymerization initiator is not particularly limited, but examples include organic peroxides such as benzoyl peroxide and t-butylperoxy-2-ethylhexyl monocarbonate. One polymerization initiator may be used, or two or more polymerization initiators may be used in combination.

[0051] The weight-average molecular weight of the resin particles can be adjusted by adjusting the concentration of the polymerization initiator, using a chain transfer agent in combination, or both. Conventionally known chain transfer agents such as octyl mercaptan, dodecyl mercaptan, and α-methylstyrene dimer can be used.

[0052] The addition of acrylonitrile and styrene may be carried out in stages or continuously. The addition rate will vary depending on the capacity and shape of the polymerization apparatus, the polymerization temperature, etc., and should be selected as appropriate.

[0053] The foaming agent is impregnated into the resin particles by injecting it into the container under pressure during or after polymerization, raising the temperature to a level above the softening point of the resin particles, and then impregnating the resin particles.

[0054] After the impregnation of the foaming agent is complete, the resin particles are removed from the polymerization system and dehydrated and dried as necessary.

[0055] Next, a fatty acid amide is attached to the surface of the resin particle body to obtain foamed resin particles. The method for attaching the fatty acid amide to the surface of the resin particle body is not particularly limited, and for example, a method of mixing the resin particle body and the fatty acid amide in a mixer can be employed, or a method of introducing the fatty acid amide into the piping during air transport when the resin particle body is transported to a storage tank can be employed.

[0056] <<Foam particles and molded articles>> "Foamed particles" are obtained by foaming foamable resin particles, which are heated with steam or the like to form a cellular structure. Foamed particles include the foamed particle body. Since foamed particles are obtained by foaming the above-mentioned foamable resin particles, the base resin is acrylonitrile-styrene copolymer and it contains brominated styrene-butadiene copolymer. Preferably, fatty acid amides are attached to the surface of the foamed particle body. However, it is not necessary for fatty acid amides to be attached to the surface of the foamed particle body.

[0057] The surface bubble diameter of the foamed particles is between 40 μm and 60 μm. Surface bubble diameter refers to the diameter of the bubbles present on the surface of the foamed particles. If the surface bubble diameter is within this range, appearance defects can be suppressed. The lower limit of the surface bubble diameter is preferably 42.5 μm or more or 45 μm or more, and the upper limit is preferably 56 μm or less or 54 μm or less.

[0058] The amount of brominated styrene-butadiene copolymer in the foamed particles is preferably 0.2 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin constituting the foamed particles. If the amount is within the above range, blocking of the foamed particles in the molded foamed particle article and defects in the appearance of the molded article can be further suppressed. The lower limit of this amount is more preferably 0.5 parts by mass or more, 0.8 parts by mass or more, or 1.2 parts by mass or more relative to the foamed particles, and the upper limit is more preferably 5 parts by mass or less, 4 parts by mass or less, or 3 parts by mass or less relative to the resin particle body. Note that in the process of obtaining foamed particles from foamable resin particles, the composition and blending of acrylonitrile-styrene copolymer and brominated styrene-butadiene copolymer do not change, so it is considered that the amount of brominated styrene-butadiene copolymer per 100 parts by mass of base resin in the foamed resin particles is equal to the amount of brominated styrene-butadiene copolymer per 100 parts by mass of base resin in the foamed particles.

[0059] Molded articles are obtained by foaming foamed particles or foamable resin particles with steam, hot air, hot water, etc., and then molding them. Methods commonly used for foamed styrene resins can be applied for foaming and molding. For example, a method can be applied in which foamed particles, pre-foamed with steam, are filled into a mold with small holes, and then reheated with steam, etc., to form the product.

[0060] The molded product is suitable for applications requiring heat resistance, oil resistance, and chemical resistance, such as automotive interior materials, packaging materials, and heat insulation components for electrical appliances.

[0061] According to this embodiment, since the foamed resin particles contain a brominated styrene-butadiene copolymer as a flame retardant and the moisture content of the foamed resin particles is 1% by mass or less, blocking of the foamed resin particles can be suppressed when the foamed resin particles are foamed, and defects in the appearance of the molded article when molded using these foamed particles can be suppressed.

[0062] This is thought to be based on the following findings: Blocking of foamed resin particles when foaming, and defects in the appearance of molded products when using foamed resin particles, are thought to be caused by the reduction of surface bubble diameter (surface cell diameter), which makes the surface of the foamed resin particles more prone to melting during foaming.

[0063] The inventors conducted further intensive research and found that when conventional flame retardants are used, the surface bubble diameter tends to become finer, and that the reason for the finer bubble diameter in foamed particles is that the flame retardant used in the production of the foamed resin particles increases the moisture content of the foamed resin particles, and this moisture acts as a nucleation point for bubbles, resulting in the finer surface bubbles of the foamed particles. Therefore, in the present invention, by using a specific flame retardant, brominated styrene-butadiene copolymer, to reduce the moisture content of the foamed resin particles, the surface bubble diameter of the resulting foamed particles can be increased, thereby suppressing the blocking of foamed particles and suppressing defects in the appearance of the molded article.

[0064] According to this embodiment, a fatty acid amide with a melting point of 60°C to 140°C is attached to the surface of the foamed particle body, and it is preferable that the amount of fatty acid amide attached is 0.01 parts by mass or more and 0.15 parts by mass or less per 100 parts by mass of the resin particle body. Furthermore, when the ratio (X / Y) of the amount of brominated styrene-butadiene copolymer blended (X) to the amount of fatty acid amide attached (Y) is 10 to 100, the length of the molten area when a fire run test is performed on the molded article can be further reduced. This is based on the following findings. When foamed resin particles are foamed with fatty acid amide attached to the surface of the resin particle body, cracks are formed during the foaming process and the cooling process of the foamed particles after foaming, and the foaming agent remaining in the bubbles of the foamed particles is released from inside the bubbles to the outside. Here, since the foaming agent is an organic component, it is thought that releasing the foaming agent to the outside of the foamed particles through the cracks makes it less likely for the fire run phenomenon to occur. In particular, since flame retardancy is required for fatty acid amides, it is preferable to apply them to foamed resin particles containing flame retardants such as brominated styrene-butadiene copolymers, as this can further improve flame retardancy.

[0065] Furthermore, by attaching fatty acid amides to the surface of the resin particles, the foaming agent is released from within the bubbles during the foaming process and the cooling process of the foamed particles after foaming. This allows for a rapid decrease in the internal pressure of the foamed particles after they have sufficiently fused together, thereby shortening the cooling time. This also allows for a reduction in molding time. [Examples]

[0066] To illustrate the present invention in detail, examples are given below, but the present invention is not limited to these descriptions. Figure 1 is a scanning electron microscope (SEM) image of foamed particles according to Example 1, Figure 2 is an SEM image of foamed particles according to Comparative Example 2, Figure 3 is an SEM image of foamed particles according to Comparative Example 3, and Figure 4 is an SEM image of foamed particles according to Comparative Example 4. Figure 5 is a photograph of the molded article according to Example 1, and Figure 6 is a photograph of the molded article according to Comparative Example 1. Figure 7A is an SEM image of foamed particles according to Example 8 observed at a magnification of 60x, Figure 7B is an SEM image of foamed particles according to Example 8 observed at a magnification of 100x, Figure 8A is an SEM image of foamed particles according to Example 10 observed at a magnification of 60x, and Figure 8B is an SEM image of foamed particles according to Example 10 observed at a magnification of 100x.

[0067] <Example 1> In a 50-liter autoclave equipped with a stirrer, 17.8 kg of pure water, 69.3 g of tricalcium phosphate (manufactured by Taihei Chemical Industry Co., Ltd.) as a suspension agent, 1.3 g of sodium tetradecenesulfonate (Lion Corporation's "Liporan LB440") and 0.4 g of disodium dodecyldiphenyl ethersulfonate (Kao Corporation's "Perex SSH") as surfactants, and 26.3 g of sodium acetate as an electrolyte were added and stirred at 210 rpm. Next, 3.4 kg (24 parts by mass) of acrylonitrile and 10.8 kg (76 parts by mass) of styrene were added to this aqueous phase as monomers, 17.8 g of benzoyl peroxide as a polymerization initiator, 35.5 g of t-butyl peroxy-2-ethylhexyl monocarbonate ("Perbutyl E" manufactured by NOF Corporation) as a polymerization initiator, 127.8 g of α-methylstyrene dimer as a chain transfer agent, 284 g (2.0 parts by mass) of brominated styrene-butadiene copolymer ("Emerald Innovation®" manufactured by Chemtura Japan Co., Ltd., weight-average molecular weight: 128,000, melt viscosity: 6,000 Pa·s, bromine content: 65%) as a flame retardant, and 142 g of dicumyl peroxide ("Percumyl D" manufactured by NOF Corporation) as a flame retardant aid. An organic phase containing 14.2 kg of monomers was obtained, and the temperature was raised to 90°C, and then raised to 95°C over 5 hours after reaching 90°C.

[0068] After raising the temperature to 95°C, 781g (5.5 parts by mass) of butane and 213g (1.5 parts by mass) of pentane were sequentially injected into the autoclave as blowing agents, and the temperature was raised to 115°C over 2 hours. After adding the blowing agents, the mixture was stirred at 170 rpm. After maintaining the temperature at 115°C for 6 hours, the mixture was cooled to 35°C over approximately 2 hours and 30 minutes, completing the polymerization and blowing agent impregnation process.

[0069] This resulted in the production of resin particles impregnated with a foaming agent and based on an acrylonitrile-styrene copolymer in an autoclave. The resin particles were then removed from the autoclave. Next, the resin particles were dehydrated and washed using a centrifuge.

[0070] Next, the resin particles were subjected to a classifier to extract particles with an average particle size of 0.6 to 1.4 mm. Then, 0.10 parts by mass of silica, 0.03 parts by mass of glycerin monostearate (GMS), and 0.02 parts by mass of hydroxyalkylamine (Antista 80FS, manufactured by Tanaka Chemical Research Institute Co., Ltd.) were added as coating agents to 100 parts by mass of the resin particles and mixed, coating the surface of the resin particles with the coating agents. This yielded foamed resin particles.

[0071] The obtained foamed resin particles were pre-foamed to a bulk expansion ratio of 40 times using a 30L batch-type foaming machine to obtain foamed particles. The obtained foamed particles were then matured by leaving them at room temperature in a silo for one day.

[0072] Subsequently, the foam particles were molded using an automatic molding machine (a molding machine "PEONY AD0907" manufactured by Kasahara Industries Co., Ltd.) to obtain a molded body. Specifically, the foam particles were filled into a mold measuring 300 mm x 300 mm x 25 mm, and steam at an initial pressure of 0.06 MPa (G) was introduced into the mold and heated for 15 seconds to cause secondary foaming and fusion of the foam particles. Then, the material was vacuum-cooled until the foam pressure reached 0.01 MPa to obtain the molded body. Note that (G) above refers to gauge pressure.

[0073] <Example 2> In Example 2, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of brominated styrene-butadiene copolymer blended was 0.1 parts by mass.

[0074] <Example 3> In Example 3, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of brominated styrene-butadiene copolymer blended was 0.3 parts by mass.

[0075] <Example 4> In Example 4, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of acrylonitrile was 23 parts by mass and the amount of styrene was 77 parts by mass.

[0076] <Example 5> In Example 5, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of acrylonitrile was 22 parts by mass and the amount of styrene was 78 parts by mass.

[0077] <Example 6> In Example 6, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of brominated styrene-butadiene copolymer was 1 part by mass.

[0078] <Example 7> In Example 7, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the amount of brominated styrene-butadiene copolymer blended was 4 parts by mass.

[0079] <Example 8> In Example 8, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that the butane content was 2.7 parts by mass and the pentane content was 0.9 parts by mass.

[0080] <Example 9> In Example 9, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 8, except that the amount of silica used as a coating agent was changed from 0.10 parts by mass to 0.25 parts by mass, and 0.05 parts by mass of oleic acid amide (Amide O, manufactured by Kao Corporation), which is a fatty acid amide, was added as a coating agent.

[0081] <Example 10> In Example 10, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 9, except that the amount of oleic acid amide was changed from 0.05 parts by mass to 0.08 parts by mass.

[0082] <Example 11> In Example 11, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 9, except that the amount of oleic acid amide was changed from 0.05 parts by mass to 0.10 parts by mass.

[0083] <Example 12> In Example 12, foamed resin particles, foamed particles, and molded articles were obtained using the same procedure as in Example 9, except that the amount of oleic acid amide was changed from 0.05 parts by mass to 0.16 parts by mass.

[0084] <Comparative Example 1> In Comparative Example 1, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that 2 parts by mass of tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) ("SR-130" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added as a flame retardant instead of brominated styrene-butadiene copolymer.

[0085] <Comparative Example 2> In Comparative Example 2, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that 2 parts by mass of triallyl isocyanurate 6-bromide ("Firecut P-660CN (FCP-660CN)" manufactured by Suzuhiro Chemical Co., Ltd.) was added as a flame retardant instead of brominated styrene-butadiene copolymer.

[0086] <Comparative Example 3> In Comparative Example 3, foamed resin particles, foamed particles, and molded articles were obtained by the same procedure as in Example 1, except that 2 parts by mass of bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone (Firecut P-65CN (FCP-65CN) manufactured by Suzuhiro Chemical Co., Ltd.) was added as a flame retardant instead of brominated styrene-butadiene copolymer.

[0087] <Comparative Example 4> In Comparative Example 4, foamable resin particles, foamed particles, and molded articles were obtained using the same procedure as in Example 1, except that the polymerization temperature after the addition of the foaming agent was changed from 115°C to 120°C.

[0088] <Number average molecular weight (Mn), weight average molecular weight measurement (Mw), Z average molecular weight (Mz)> The number-average molecular weight (Mn), weight-average molecular weight (Mw), and Z-average molecular weight (Mz) of the base resin constituting the resin particle body of each foamed resin particle in Examples 1-12 and Comparative Examples 1-4 were measured. The number-average molecular weight, weight-average molecular weight, and Z-average molecular weight were measured by dissolving the foamed resin particles in THF (tetrahydrofuran) and measuring them by GPC (gel permeation chromatography), and calibrated with standard polystyrene. The above GPC analysis was performed using the following equipment: Tosoh Corporation "SC-8020" type, two Showa Denko K.K. "Shodex AC-80M" columns connected in series, column temperature: 40°C, flow rate: 1.0 ml / min, and Tosoh Corporation "UV-8020" ultraviolet-visible light detector.

[0089] <Moisture content measurement> The moisture content of each foamed resin particle in Examples 1-12 and Comparative Examples 1-4 was measured using a Karl Fischer moisture meter. Specifically, the foamed resin particles were heated at 160°C using a "Moisture Vaporizer CHK-501" manufactured by Kyoto Electronics Manufacturing Co., Ltd. to vaporize the moisture, and the moisture content was measured using a "Karl Fischer Moisture Meter (Coulometric Titration Method) MKC-610" manufactured by Kyoto Electronics Manufacturing Co., Ltd.

[0090] <Effervescent> The foaming properties of each foamable resin particle from Examples 1 to 12 and Comparative Examples 1 and 4 were evaluated based on the bulk density when foamed using a shelf-type foaming machine and the time required for foaming when foamed using a pre-foaming device.

[0091] The foaming properties using a shelf-type foaming machine were evaluated as follows: First, steam at a gauge pressure of 3 kPa(G) was supplied into the shelf-type foaming machine (manufactured by FESTO) and heated for 270 seconds to foam the foamable resin particles and obtain foamed particles. Next, the foamed particles were air-dried at room temperature for one day.

[0092] These foamed particles were filled into a graduated cylinder so that they would naturally accumulate, and the bulk volume (in L) of the foamed particle group was read from the scale of the graduated cylinder. Then, the mass (in g) of the foamed particle group in the graduated cylinder was divided by the aforementioned bulk volume, and the bulk density (in kg / m³) of the foamed particles was obtained by further unit conversion. 3 The bulk density of the foamed particles measured in this way is shown in the "Shelf-type foaming" column of Tables 1 and 2. In evaluating foaming properties using a shelf-type foaming machine, a lower bulk density indicates better foaming performance.

[0093] <Blocking Rate Measurement> The foamed particles from Examples 1-5, 8-12, and Comparative Examples 1 and 4 were sieved using a sieve with a mesh size of 10 mm, and clumps of foamed particles formed by blocking were removed. The blocking rate was defined as the mass ratio of the clumps of foamed particles formed by blocking to the total mass of foamed particles after foaming. In evaluating the blocking rate, a lower blocking rate is preferable as it indicates that blocking is suppressed, but a blocking rate of 4% or less can be considered good.

[0094] <Surface bubble diameter measurement> The surface bubble diameters of each foamed particle in Examples 1-12 and Comparative Examples 1-4 were measured. Specifically, the foamed particles were cut in half using a feather blade. Next, with the cross-section of the foamed particle facing upwards, the cross-section was observed using a low-vacuum scanning electron microscope (Hitachi High-Tech Science Co., Ltd. "Miniscope(registered trademark) TM3030Plus") (see Figures 1-4). For the surface bubbles of the foamed particles (bubbles located on the outermost side), the area of ​​the cross-section of each bubble was measured using image analysis software, and the diameter of a virtual circle with the same area was defined as the bubble diameter of each bubble, and this was defined as the surface bubble diameter. The surface bubble diameter was the arithmetic mean of the values ​​measured for 10 bubbles.

[0095] <Fusion rate> Each molded product according to Examples 1-12 and Comparative Examples 1-4 was cut in the longitudinal direction (300 mm direction) near the center (150 mm position), and the fracture surface was observed visually. The ratio (percentage) of the number of foam particles that fractured from inside the foam particles to the total number of foam particles on the fracture surface was calculated and defined as the fusion rate (%).

[0096] <Measurement of cooling time> When obtaining the molded articles according to Examples 1-5, 8-12 and Comparative Examples 1 and 4, the foam was vacuum-cooled until the foam pressure reached 0.01 MPa. The vacuum cooling time at this time was measured as the cooling time.

[0097] <Appearance of the molded product> The appearance of the molded articles from Examples 1-12 and Comparative Examples 1-4 was evaluated. The evaluation criteria were as follows. A: The appearance of the molded product was good. B: The molded part melted, and a defect in appearance was confirmed.

[0098] <Molded object density> The density was calculated for each molded body according to Examples 1 to 12 and Comparative Examples 1 to 4. Specifically, a plate-shaped test piece measuring 50 mm in length, 50 mm in width, and 25 mm in thickness was cut from each molded body. The density of the molded body (in g / L) was calculated by dividing the mass (in g) of this test piece by its volume (in L) and then converting the units.

[0099] <Measuring combustion rate> The flammability test specified in FMVSS No. 302 was performed on each molded body according to Examples 1-12 and Comparative Examples 1-4, and the burning rate (FMVSS) was measured. First, a plate-shaped test piece measuring 350 mm in length, 65 mm in width, and 12.7 mm in thickness was cut from the molded body and cured at 60°C for two days. On the cured test piece, a start line was drawn 38.1 mm away from the base end in the longitudinal direction, and an end line was drawn 254 mm away from this base end. Using this test piece, a flammability test was performed in the same manner as FMVSS No. 302, with the burner flame touching the test piece. In the flammability test, the flame was applied to the test piece for 15 seconds, then the flame was moved away, and timing was started when the flame reached the start line. The burning time was defined as the time required to pass between the start line and the end line. The burning distance was defined as the distance between the start line and the end line. This flammability test was performed 10 times, and the average value of the burning rate was calculated based on these test results and defined as the burning rate. The burning rate of the test specimen was calculated using the following formula (1). In formula (1), the symbol B represents the burning rate (unit: mm / min), the symbol D represents the distance the flame traveled (unit: mm), and the symbol T represents the time required for the flame to travel D mm (unit: seconds). B = 60 × D / T …(1)

[0100] In the event that the test specimen self-extinguished, the combustion rate was treated as 0 mm / min. Here, the test specimen was judged to have self-extinguished if "the test specimen did not ignite," "the combustion of the test specimen ended before reaching the starting position for combustion time measurement (i.e., the starting line mentioned above)," or "the combustion of the test specimen ended within 60 seconds of reaching the starting position for combustion time measurement, and the distance from the starting position to the end position of combustion was within 50.8 mm."

[0101] <Digestion time> For each molded article in Examples 1-12 and Comparative Examples 1-4, a flammability test was performed in accordance with measurement method A of JIS A 9521:2022 (Method A), and the extinguishing time was measured. First, five plate-shaped test pieces measuring 200 mm in length, 25 mm in width, and 10 mm in thickness were cut from the molded article. A flammability test was performed on each test piece, and the average extinguishing time of the five test pieces was calculated and defined as the flame extinguishing time.

[0102] <Fire-running test evaluation> A fire-running test was performed on the molded bodies according to Examples 1-12 and Comparative Examples 1-4 for evaluation. Specifically, a plate-shaped test piece measuring 350 mm in length, 65 mm in width, and 25 mm in thickness was cut from the molded body, and this test piece was cured at 40°C for one day. After curing, the test piece was fixed at a 10° inclination so that one end in the longitudinal direction was downward and the other end was upward. A flame was applied to the lower end of the test piece in the longitudinal direction for one second, and the flame was immediately removed. The propagation of the flame along the surface of the test piece was observed, and the length of the molten area was measured. If the molded body did not ignite, the length was recorded as 0 mm.

[0103] <Heat resistance> The heat resistance of the molded articles according to Examples 1-12 and Comparative Examples 1 and 4 was evaluated. Specifically, first, a plate-shaped test piece measuring 50 mm in length, 50 mm in width, and 25 mm in thickness was cut from the molded article, and this test piece was cured at 23°C for one day. Then, the dimensions of each part of the length and width of the test piece were measured to two decimal places using calipers. Next, the test piece after dimensional measurement was held in a forced-circulation oven set to 90°C for 22 hours (approximately one day). After that, the test piece was removed from the oven and left to stand at a temperature of 23°C for one day. Next, the dimensions of the same parts as before heating were measured, and the heating dimensional change rates for length and width were calculated using the following formula (2), and the arithmetic mean was taken as the heating dimensional change rate. Percentage change in dimensions due to heating (%) = (Dimensions before heating - Dimensions after heating) × 100 / Dimensions before heating ... (2)

[0104] Next, the rate of dimensional change during heating was evaluated. The evaluation criteria were as follows: A: The dimensional change rate during heating was within 1%, indicating excellent heat resistance. B: The dimensional change rate during heating was between 1% and 2%, indicating slightly inferior heat resistance. C: The dimensional change rate during heating exceeded 2%, indicating extremely poor heat resistance.

[0105] The results are shown in Tables 1 and 2 below. [Table 1]

[0106] [Table 2]

[0107] As shown in Table 2, the foamed resin particles in Comparative Examples 1 to 4 did not contain brominated styrene-butadiene copolymer (Emerald Innovation® 3000, manufactured by Chemtura Japan Co., Ltd.) as a flame retardant, and the moisture content of the foamed resin particles exceeded 1% by mass. As a result, a high blocking rate of the foamed particles or defects in the appearance of the molded articles were observed (see Figure 6).

[0108] In contrast, as shown in Table 1, the foamed resin particles in Examples 1 to 12 contained brominated styrene-butadiene copolymer as a flame retardant, and the moisture content of the foamed resin particles was 1% by mass or less, resulting in a low blocking rate of the foamed particles and a good appearance of the molded article (see Figure 5). Furthermore, the surface bubble diameter of the foamed particles in Examples 1 to 12 was larger than that of the foamed particles in Comparative Examples 1 to 4, indicating that the effects of the present invention can be obtained within a specific range. Thus, it was confirmed that by containing brominated styrene-butadiene copolymer as a flame retardant in the foamed resin particles and keeping the moisture content of the foamed resin particles at 1% by mass or less, blocking of the foamed particles can be suppressed, and defects in the appearance of the molded article can also be suppressed.

[0109] Furthermore, since the foamed resin particles in Example 8 did not contain oleic acid amide (Amide O, manufactured by Kao Corporation), which is a fatty acid amide, the length of the molten portion of the molded body in the fire run test was 200 mm. However, since the foamed resin particles in Examples 9 to 12 contained oleic acid amide, which is a fatty acid amide, the length of the molten portion of the molded body in the fire run test was shorter than that of Example 8. This confirmed that the foamed resin particles can reduce the length of the molten portion of the molded body in the fire run test by attaching fatty acid amide to the surface of the resin particle body, which is based on an acrylonitrile-styrene copolymer.

[0110] Furthermore, when the foamed particles from Example 8 and Example 10 were observed at 60x and 100x magnification, respectively, using a low-vacuum scanning electron microscope (Miniscope™ TM3030Plus manufactured by Hitachi High-Tech Science Corporation) (see Figures 7A, 7B, 8A, and 8B), cracks were observed in Example 10, in which oleic acid amide was added (see Figure 8B), whereas no cracks were observed in Example 8, in which oleic acid amide was not added (see Figure 7B).

Claims

1. A foamed resin particle comprising a resin particle body with an acrylonitrile-styrene copolymer as the base resin and a foaming agent, The foamed resin particles contain a brominated styrene-butadiene copolymer. Foamed resin particles having a moisture content of 1% by mass or less.

2. The foamed resin particles according to claim 1, wherein the amount of the brominated styrene-butadiene copolymer blended is 0.2 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin.

3. The foamed resin particles according to claim 1, wherein the amount of the brominated styrene-butadiene copolymer blended is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the base resin.

4. The foamed resin particles according to claim 1, wherein the acrylonitrile component content in the acrylonitrile-styrene copolymer is 10% by mass or more and 50% by mass or less.

5. The foaming resin particles according to claim 1, wherein the foaming agent comprises pentane and butane.

6. The foamable resin particle according to claim 1, wherein a fatty acid amide is attached to the surface of the resin particle body, and the melting point of the fatty acid amide is 60°C or higher and 140°C or lower.

7. The foamable resin particles according to claim 6, wherein the ratio (X / Y) of the amount of brominated styrene-butadiene copolymer blended (X) to the amount of fatty acid amide attached (Y) is 10 or more and 100 or less.

8. Foamed particles using acrylonitrile-styrene copolymer as a base resin, The foamed particles contain a brominated styrene-butadiene copolymer. Foamed particles having a surface bubble diameter of 40 μm or more and 60 μm or less.

9. The foamed particle according to claim 8, wherein the amount of the brominated styrene-butadiene copolymer blended is 0.2 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin.

Citation Information

Patent Citations

  • Foamable resin particles, pre-foamed particles, and shaped foam

    WO2020184007A1